NIR reflective pigments for cool roof applications: A comprehensive review. (1st September 2021) - Rosati, Andrea; Fedel, Michele; Rossi, Stefano
Abstract: We performed a comprehensive review of the state of the art of synthesis methods for pigments employed for cool roof. The aim is to present the best synthesis method, among those proposed, in terms of energy and raw materials costs. In particular, inorganic NIR reflective pigments not containing metals that can adversely affect the environment and human health are considered. This manuscript aims to be a practical instrument for selecting pigments, taking into account the following parameters: colorimetric parameters, near-infrared reflectance values, energy-saving, and limited waste synthesis routes. Graphical abstract: Image 1 Highlights: Near-infrared reflective pigments different from TiO2 and based on non-toxic metals are considered to realize cool roofs. Sol-Gel and hydrothermal routes are confirmed as routes to obtain high-performance pigments. Rare earth oxides-based pigments resulted promising to obtain pigments with high near-infrared reflectance.